Imitation of MSME Transaction Documents as a Form of Business Identity Misuse: A Socio-Legal Analysis of the Gap Between Norms and Practices - Eghi Hendri Rifaldo Purba; Martono Anggusti; Samuel Frans Boris Situmorang (PT FORMOSA CENDEKIA GLOBAL, 2026)
The counterfeiting of Micro, Small, and Medium Enterprise (MSME) transaction documents—a form of business identity misuse—is a crime that has emerged alongside the accelerated digital transformation of economic activities. This study aims to comprehensively analyze the gap between legal norms (*das sollen*) and social practices (*das sein*) regarding the protection of MSME business identities, employing a socio-legal approach. The research methodology combines a normative-juridical approach with a socio-legal perspective. This approach views law not merely as written norms (